The Effect of Critical Thinking Ability, Emotional Intelligence, and Learning Independence on Mathematics Learning Outcomes of Class VIII Students of SMP Negeri 1 Sungguminasa - Musa, Hastuty; Rusli; Lince, Ranak; Gaffar, Abdul; Jusnawati (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
The purpose of this study was conducted to determine: (1) how is the description of critical thinking skills, emotional intelligence and learning independence of grade VIII students of SMP Negeri 1 Sungguminasa. (2) whether there is an influence on the ability to think critically, emotional intelligence and independent learning together on the mathematics learning outcomes of class VIII students of SMP Negeri 1 Sungguminasa. (3) whether there is a positive influence on the ability to think critically on the mathematics learning outcomes of grade VIII students of SMP Negeri 1 Sungguminasa. (4) whether there is a positive effect of emotional intelligence on the mathematics learning outcomes of grade VIII students of SMP Negeri 1 Sungguminasa. (5) whether there is a positive effect of independent learning on the mathematics learning outcomes of grade VIII students of SMP Negeri 1 Sungguminasa. This type of research is an ex-post facto research which is causality with a research sample of 57 students from class VIII SMP Negeri 1 Sungguminasa in the 2019/2020 school year using the sampling technique using cluster random sampling method. Data collection techniques using tests, questionnaires and documentation. The data analysis technique used descriptive statistics and inferential statistical analysis. The results showed that: (1) critical thinking skills, emotional intelligence and learning independence of class VIII students of SMP Negeri 1 Sungguminasa were in the good category while the mathematics learning outcomes of grade VIII students of SMP Negeri 1 Sungguminasa were in very high criteria. (2) the ability to think critically, emotional intelligence and independent learning together have an effect on the mathematics learning outcomes of grade VIII students of SMP Negeri 1 Sunggguminasa. (3) the ability to think critically has a positive effect on the mathematics learning outcomes of grade VIII students of SMP Negeri 1 Sungguminasa. (4) emotional intelligence has a positive effect on the mathematics learning outcomes of grade VIII students of SMP Negeri 1 Sungguminasa. (5) independent learning has a positive effect on mathematics learning outcomes of class VIII students of SMP Negeri 1 Sungguminasa.